2017
DOI: 10.25125/agriculture-journal-ijoear-sep-2017-10
|View full text |Cite
|
Sign up to set email alerts
|

The utilities of Citrus tissue culture

Abstract: Abstract-Citrus is the third most important fruit crop in the world

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 75 publications
0
1
0
1
Order By: Relevance
“…Nesse processo, é possível a obtenção de haploides e duplo haploides em uma única etapa, obtendo-se assim, indivíduos homozigotos, que irão aumentar a eficiência dos programas de melhoramento genético (GERMANÁ, 2020). A produção de calos embriogênicos em citros pode ser produzida pela cultura in vitro de nucelos excisados, óvulos abortivos, óvulos não fertilizados, óvulos não desenvolvidos, anteras, estilos e estigmas, epicótilos, cotilédones e segmentos de raiz (CHAMANDOOSTI, 2017).…”
Section: Introductionunclassified
“…Nesse processo, é possível a obtenção de haploides e duplo haploides em uma única etapa, obtendo-se assim, indivíduos homozigotos, que irão aumentar a eficiência dos programas de melhoramento genético (GERMANÁ, 2020). A produção de calos embriogênicos em citros pode ser produzida pela cultura in vitro de nucelos excisados, óvulos abortivos, óvulos não fertilizados, óvulos não desenvolvidos, anteras, estilos e estigmas, epicótilos, cotilédones e segmentos de raiz (CHAMANDOOSTI, 2017).…”
Section: Introductionunclassified
“…Grosser et al (1988) reported that protoplasts can be isolated from friable embryogenic ovule-derived calli maintained on growth-regulator-free media. Chamandoosti (2017) reported that the production of embryogenic callus lines in citrus can be produced by the in vitro culture of excised nucelli, abortive ovules, unfertilized ovules, undeveloped ovules, juice vesicles, anthers, styles and stigmas, epicotyls, cotyledons, and root segments.Thus, for researches specifically focused on variety or rootstock improvements using somatic hybridization in citrus, a reliable callus induction protocol is essential. However, the efficiency of existing protocols may vary depending on the genotype used.…”
mentioning
confidence: 99%